An Inca account of the conquest of Peru/ by titu cusi Yupanqui ; translated and edited by Ralph Bauer. - Yupangui, Diego de Castro, titu cussi, active 16th century (University Press of Colorado, 2005)
The penultimate ruler of the Inca dynasty narrated this first hand account of the Spanish invasion of Peru to a missionary in 1570. This is the first English edition.